Comparative efficacy and safety of tislelizumab and pembrolizumab in advanced squamous non-small cell lung cancer: a systematic review and meta-analysis - Kevin Tandarto; Eko Adhi Pangarsa; Daniel Rizky; Budi Setiawan; Damai Santosa; Ika Kartiyani; Vina Yunarvika; Desta Nur Ewika Ardini; Damianus Galih Panunggal; Catharina Suharti (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Immunotherapy with immune checkpoint inhibitors (ICIs) has transformed the management of squamous non-small cell lung cancer (sqNSCLC). Two leading agents, pembrolizumab and the novel anti–PD-1 antibody tislelizumab, have demonstrated promising outcomes; however, direct comparisons between them remain limited. In this systematic review and meta-analysis of phase II/III clinical trials published up to July 2025, the efficacy and safety of these agents were evaluated. Both pembrolizumab and tislelizumab significantly improved overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) compared with chemotherapy. However, tislelizumab showed modest advantages, including slightly improved PFS (HR 0.66 vs. 0.71), higher ORR (OR 1.82 vs. 1.75), and a lower incidence of grade ≥3 adverse events (24.3% vs. 28.9%). Overall survival remained comparable between the two treatments. These findings suggest the potential of tislelizumab as a competitive alternative to pembrolizumab, particularly in patients with poor performance status or multiple comorbidities. Nevertheless, the lack of direct head-to-head trials limits definitive conclusions and highlights the need for further comparative studies.